USULAN STRATEGI PEMASARAN DALAM RANGKA MENINGKATKAN PENJUALAN DI PT. X - Yosefa Yosefa (Business Administration Department - Universitas Katolik Parahyangan, 2021)
PT. X has been around for 26 years and is the sole distributor for 3 well-known furniture brands. This does not make PT. X can market products easily. The decline in sales of PT. X, has occurred from 2016 to 2020. In fact, the average economic growth in the marketing area of PT. X tends to be stable at the level of 4.66% - 7.66%. This study aims to look at the marketing strategies that have been executed by the PT. X (segmenting, targeting, positioning, marketing mix) and analyze the internal and external environment of PT. X (using the company's internal analysis, PESTLE Analysis and Porter's Five-Forces Model) in order to get a recommendation marketing strategy in accordance with the condition of PT. X to increase the sales. Recommended strategies from analysis The Competitive Profile Matrix (CPM), which produces 8 alternative strategies and The Strength-Weaknesses-Opportunities-Threats (SWOT) Matrix which produces 22 strategies. These alternative strategies were analyzed more deeply and obtained 4 prioritized strategies to be implemented in PT. X. Keywords: Marketing Strategy, Marketing Mix, CPM, SWOT Matrix